The impact of perceived risk, screening eligibility and worry on preference for lung cancer screening: a cross-sectional survey. Issue 1 (16th March 2020) - See, Katharine; Manser, Renee; Park, Elyse R.; Steinfort, Daniel; King, Bridget; Piccolo, Francesco; Manners, David
Lung cancer screening is effective at reducing lung cancer deaths when individuals at greatest risk are screened. Recruitment initiatives target all current and former smokers, of whom only some are eligible for screening, potentially leading to discordance between screening preference and eligibility in ineligible individuals. The objective of the present study was to identify factors associated with preference for screening among ever-smokers. Ever-smokers aged 55–80 years attending outpatient clinics at three Australian hospitals were invited. The survey recorded: 1) demographics; 2) objective lung cancer risk and screening eligibility using the Prostate Lung Colon Ovarian 2012 risk model; and 3) perceived lung cancer risk, worry about and seriousness of lung cancer using a validated questionnaire. Multivariable ordinal logistic regression identified predictors of screening preference. The survey was completed by 283 individuals (response rate 27%). Preference for screening was high (72%) with no significant difference between low-dose computed tomography screening-eligible and -ineligible individuals (77% versus 68%, p=0.11). Worry about lung cancer (adjusted-proportional odds ratio (adj-OR) 1.31, 95% CI 1.08–1.58; p=0.007) and perceived seriousness of lung cancer (adj-OR 1.31, 95% CI 1.05–1.64; p=0.02) were associated with higher preference for lung cancer screening while screening eligibility was not. The concept of "early detection" was the most important driver to have screening while practical obstacles like difficulty travelling to the scan or taking time off work were the least important barriers to screening. Most current or former smokers prefer to undergo screening. Worry about lung cancer and perceived seriousness of the diagnosis are more important drivers for screening preference than eligibility status. Preference for lung cancer screening is high among Australian current and former smokers. Worry about lung cancer and perceived seriousness of the disease are associated with screening preference, while eligibility based on lung cancer risk is not. http://bit.ly/36PZlYA